2015
DOI: 10.1002/jcp.25285
|View full text |Cite
|
Sign up to set email alerts
|

AllTrans-Retinoic Acid Mediates MED28/HMG Box-Containing Protein 1 (HBP1)/β-Catenin Signaling in Human Colorectal Cancer Cells

Abstract: Vitamin A is required for normal body function, including vision, epithelial integrity, growth, and differentiation. All trans-retinoic acid (ATRA), a family member of vitamin A, has been explored in treating acute promyelocytic leukemia and other types of cancer. Dysregulated Wnt/β-catenin signaling and disrupted cadherin-catenin complex often contribute to colorectal malignancy. MED28, a mammalian Mediator subunit, is found highly expressed in breast and colorectal cancers. Our laboratory has also reported t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…In addition to NSCLC, our group has previously identified a role of MED28 in the malignancy of breast cancer as indicated by its effect on migration and invasion, as well as cell morphology of human breast cancer cells (Huang et al, ; Huang et al, ). Moreover, we have also reported that MED28 is involved in cell growth in both human breast cancer cells and colorectal cancer cells (Huang et al, ; Lee et al, ). Our findings further emphasize the significance of MED28 and imply the prospective translational application of MED28 in tumorigenesis and cancer development.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In addition to NSCLC, our group has previously identified a role of MED28 in the malignancy of breast cancer as indicated by its effect on migration and invasion, as well as cell morphology of human breast cancer cells (Huang et al, ; Huang et al, ). Moreover, we have also reported that MED28 is involved in cell growth in both human breast cancer cells and colorectal cancer cells (Huang et al, ; Lee et al, ). Our findings further emphasize the significance of MED28 and imply the prospective translational application of MED28 in tumorigenesis and cancer development.…”
Section: Discussionmentioning
confidence: 83%
“…For example, the expression of Mediator subunit MED15 with its clinical implications in head and neck squamous cell carcinoma has been identified (Shaikhibrahim et al, ). Recently, we have reported that MED28, another Mediator subunit, is involved in cell growth in human breast cancer cells and colorectal cancer cells (Huang et al, ; Lee, Hsieh, Huang, & Li, ). Therefore, mammalian Mediator subunits display novel cellular roles in addition to their function in transcriptional activation.…”
Section: Introductionmentioning
confidence: 99%
“…HMG box‐containing protein 1 is a member of the HMG‐box transcription factor family and functions as a transcriptional repressor. It has two important domains including the HMG box DNA‐binding domain and an AXH domain . HMG box‐containing protein 1 has been found to have tumor‐suppressive functions in multiple cancers.…”
Section: Discussionmentioning
confidence: 99%
“…G, Relationship between AFAP1-AS1 and HBP1 expression was analyzed in the profile of non-small-cell lung cancer patient tissue from Gene Expression Omnibus domain and an AXH domain. 35 HMG box-containing protein 1 has been found to have tumor-suppressive functions in multiple cancers. For instance, HBP1 overexpression sensitizes prostate cancer cells to radiation and increases apoptosis in prostate cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the retinoid receptor genes are not mutated in the majority of human cancer specimens indicates that epigenetic events could be involved. Studies have reported that RARβ can be repressed by hypermethylation and histone deacetylation in some types of cancer, resulting in an associated resistance to the growth inhibitory effects of retinoic acid in some cancer types [35][36][37].…”
Section: Discussionmentioning
confidence: 99%